"Artistic Representations of the Image of the Revolution in Algerian Novelistic Discourse: The Novels of Tahar Wattar as a Case Study" - saidani, naase (El Omda in Linguistics and Discourse Analysis, 2018)
The revolution has occupied a central place in the novel, shaping the narrative space through the act of remembering and the flow of memory. Time is the master of storytelling, and the narrative text is nothing but an aesthetic product of a temporally realized reality, defined within a visionary cognitive framework. In constructing the narrative discourse, Tahar Wattar writes history within an aesthetic context, based on his imaginative or interpretive vision of history—not as a defense of the past, nor as an attachment to it to the point of sanctification or resentment. Rather, the writing of history in the novel must be conscious of forming history as reality and shaping reality as history, in response to the dialectical relationship between presence and absence, between the self and the other.